1980
DOI: 10.1111/j.1600-0447.1980.tb00583.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric symptoms in ruptured anterior communicating aneurysms: social prognosis

Abstract: Pre- and postoperative psychiatric symptoms were compared in 85 patients with anterior communicating aneurysms and 73 of these cases were followed up to determine the long-term results. Psychiatric symptoms of varying severity were present preoperatively in 61 % of the cases, which decreased to 34 % after surgery. Use of the microsurgery microscope resulted in a no change: aggravation:mortality ratio of 27:5:0, as compared with 33:20:4 when the microscope was not used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Treatment options to improve the cognitive impairments following aneurysm rupture are strongly needed. In patients with the so‐called ACoA syndrome, cognitive or psychiatric residuals are frequently found, often with a pervasive negative impact on the patient's life (Okawa et al. , 1980; Stenhouse et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment options to improve the cognitive impairments following aneurysm rupture are strongly needed. In patients with the so‐called ACoA syndrome, cognitive or psychiatric residuals are frequently found, often with a pervasive negative impact on the patient's life (Okawa et al. , 1980; Stenhouse et al.…”
Section: Discussionmentioning
confidence: 99%
“…, 2002). Depending on the patient characteristics and the neuropsychological tests and criteria used, 40–70% of this patient group is estimated to retain severe cognitive deficits (Okawa et al. , 1980; Stenhouse et al.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, other studies could not find any relationship between side of aneurysm and postoperative performance (De Santis et al 1989, Maurice-Williams et al 1991, Tidswell et al 1995. Anterior communicating artery (AcoA) aneurysmal SAH has been found, in several studies, to be associated with changes in personality, intellectual function, memory and conceptual learning, and with poor social adjustment (Sengupta et al 1975, Okawa et al 1980, Stenhouse et al 1991. In contrast to these findings, Hü tter et al (1995) found no statistically significant differences between AcoA patients and patients with other aneurysm locations.…”
Section: Outcomementioning
confidence: 97%
“…Anterior communicating artery (AcoA) aneurysmal SAH has been found, in several studies, to be associated with changes in personality, intellectual function, memory and conceptual learning, and with poor social adjustment (Sengupta et al. 1975, Okawa et al. 1980, Stenhouse et al.…”
Section: Outcomementioning
confidence: 99%
“…Some studies reported little or no persisting significant neuropsychological deficits in uncomplicated SAH 2-4 while others indicated that deficits do occur and are caused by global [5][6][7][8][9][10][11][12][13][14] or focal brain damage. 10,[15][16][17] These varieties in the study results may be caused by differences in the clinical state of the patients immediately following the ictus, i.e., the strength of the bleeding besides the possibility of aneurysm site playing a role in the outcome of SAH. The effect of aneurysm location on outcome is not fully explored.…”
Section: Introductionmentioning
confidence: 88%